Do we start too late? Insights from the real-world non-interventional BALANCE study on the present use of levodopa/carbidopa intestinal gel in advanced Parkinson's disease in Germany and Switzerland. (October 2022) - Weiss, Daniel; Ebersbach, Georg; Möller, Jens Carsten; Schwarz, Johannes; Arlt, Carolin; Fritz, Björn; Sensken, Sven-Christian; Eggert, Karla
Abstract: Introduction: Advanced Parkinson's disease is characterized by motor and non-motor fluctuations to oral dopamine replacement therapy. The BALANCE study evaluated the clinical practice in Germany and Switzerland, when patients eligible for levodopa/carbidopa intestinal gel (LCIG) therapy decided to either switch to LCIG or to stay on optimized standard of care (SoC) oral therapy as a non-randomized regular clinical decision. Methods: In this non-interventional, multicenter, prospective observational study, patients were recruited between 2015 and 2020. We obtained comprehensive baseline characteristics in both groups. As primary endpoint, we evaluated whether LCIG led to higher quality-of-life (QoL) improvement than SoC after 12 months. As secondary endpoints, we studied several motor and non-motor outcomes. Results: About half of the 137 patients decided for LCIG treatment (n = 73, 53.5%). Those were aged >70 years more often, had more advanced disease stage, higher burden of motor and neuropsychiatric symptoms, and cognitive impairment including dementia compared to SoC. QoL change after 12 months did not differ between groups ( P  = 0.286). The LCIG group improved in secondary outcomes, including the UPDRS III in ON, UPDRS IV, Unified Dyskinesia Rating Scale, and Non-Motor Symptoms Scale. Clinical Global Impression-Improvement scale improved in 78.0% and 19.5% of patients receiving LCIG and SoC, respectively. Caregiver burden remained stable in LCIG but worsened with SoC. Conclusion: In current practice, patients and physicians delayed LCIG treatment and started substantially beyond the established indication criteria. This practice bears the risk to produce inferior results compared to the results from existing high-level evidence. Highlights: In present clinical practice patients and physicians use LCIG late. This practice is in contrast to the available randomized controlled trial. Quality of life is lower and treatment-emergent adverse effects higher with this practice. Nevertheless, some motor and non-motor outcomes may improve after 12 months with LCIG. LCIG should not be delayed for too long, once the established indication criteria have been met.